An Overview of Transdisciplinary and Bottom-up Approach for Urban Resilience: The Case of Turkey - Esen Özdamar; Ertuğ Önay (Environmental Science and Sustainable Development, 2024)
While top-down strategies have traditionally dominated urban planning in Turkey, recent shifts towards participatory practices and project-based policies have aimed to involve citizens in decision-making processes. Nevertheless, in the case of Turkey, these participatory models are inadequate for effectively addressing resilience. This article therefore discusses the role of participatory processes in creating resilient cities, as well as how to strengthen transdisciplinary (TR) and bottom-up approaches to urban participation in Turkish urban contexts. The article presents a theoretical framework that connects TR and bottom-up approaches based on existing literature, practices, and planning policy examples. It argues that TR approaches complement bottom-up approaches to urban governance by enhancing urban and social resilience, strengthening local communities, and reducing urban inequalities. Urban planning efforts that promote collaboration, incorporate multiple perspectives, and involve local communities in decision-making processes can address complex urban issues while also fostering long-term sustainability and resilience. This approach not only instills a sense of ownership and empowerment among urban residents but also leverages knowledge and skills to generate more effective and sustainable solutions. By creating a framework that promotes long-term education and citizenship awareness, urban governance can sustain urban resilience in a more viable manner over the long term in Turkey.